PENERAPAN PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA DI KELAS IVB MI MUHAMMADIYAH KALOSI - Sitti Maryam Maulid; Muh. Idham Haliq; Dedi Setiawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the low learning outcomes of students in the Natural Science (IPA) subject in class IVB of MI Muhammadiyah Kalosi, where 53% of students had not yet achieved the Learning Objective Attainment Criteria (KKTP). This study aims to describe the implementation of differentiated learning and to determine the improvement in student learning outcomes. The method employed is Classroom Action Research (CAR) using the Kemmis and McTaggart model, carried out in two cycles, each consisting of planning, action implementation, observation, and reflection. The research subjects were 15 students of class IVB. Data collection techniques involved observation, learning outcome tests, and documentation. The results indicate that differentiated learning can improve student learning outcomes, as demonstrated by an increase in learning completeness from 33% in the pre-action phase to 54% in cycle I, and further rising to 87% in cycle II, thereby exceeding the established success indicator of ≥85%. This is accompanied by an increase in student activeness and engagement in the learning process. It is concluded that differentiated learning is effective in improving student learning outcomes in the Natural Science subject and is capable of accommodating the diversity of student characteristics.